Effect of onion oil on some haematological parameters in dogs with experimentally induced hypercholesterolemia - Ercan Keskin; Zafer Durgun; Mehmet Kocabatmaz; Abdullah Eryavuz (Eurasian Journal of Veterinary Sciences)
Eight dogs, 8-10 months aged, were used in the investigation. The dogs were divided into two equal groups as control and experimental Both groups were fed diet containing 0.2% cholesterol for 16 days. At 10 th. day of this period, plasma cholesterol levels were incereased four times to begining of this period in both groups. The increases in cholesterol levels in both groups caused no roughness in erytrocytes surface After 10 th day of 16 day period, experimental group received daily 50µ1 of onion oil with 200 g of ground meat addi-ton to cholesterol-supplemented diet whereas control group continued feeding cholesterol-suplemented diet and 200 g of ground meat for six days. At the 5 th. and 6 th. days of period of onion oil administration (15 th. and 16 th. days of total period). Plasma cholesterol levels in experimental group decreased slightly higher than control group and before onion oil administation, while plasma glucose level decreased significantly as compared to before onion oil administration and the same sampling time of control group (P<0,05) In the study, before and after hypercholesterolemia and after onion oil administration, it was not determined striking changes in respect of erythrocytes, leucocytes counts, haemoglobine amount and haematocrit values in both groups and between groups.